Development of a High Strength Geopolymer by Novel Solar Curing. Issue 14 (1st October 2017) - Dong, Minhao; Feng, Wei; Elchalakani, Mohamed; Li, Gang (Kevin); Karrech, Ali; May, Eric F.
Abstract: Geopolymer is a popular construction material derived from different sources of aluminosilicates known for its environmental benefits and excellent durability in harsh conditions. However, the curing of fly-ash based geopolymer normally requires a thermal treatment that increases the manufacturing cost and carbon footprint. This paper explored a new economical and environmentally-friendly alternative, i.e. solar curing, that harnesses solar radiation to achieve accelerated geopolymerization process. Geopolymer mortars coated in two different greyscales namely solar curing black (SCB) and 40% black (grey, SCG) were prepared to study the effect of solar radiation absorption ability on the strength of the specimens, along with ambient cured specimens (ATC) for comparison. Mechanical properties such as workability, compressive strength, stress-strain relationship from 1 day to 28 days were tested. The SCB specimens that can easily reach 65 °C under the sun showed a substantial improvement of the compressive strength especially at the early age, i.e. 49.2 MPa at 1-day compared with 25.5 MPa for the ATC ones. At 28-day, SCB reached 92 MPa in compressive strength which is 17.8% (13.9 MPa) higher than that of ATC. SCG showed a moderate enhancement in strength. Through in-depth physical and chemical characterizations, the structure and morphology of geopolymers were identified through X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS). It was found that geopolymer cured by solar radiation had more calcium aluminate silicate content hence leading to a higher mechanical strength. Furthermore, a titration study that determines the conversion rate of the activators inside geopolymers suggested a faster geopolymerization process in the solar cured specimens. Highlights: Solar curing is a green and effective way to elevate curing temperature. Solar curing has a significant effect on geopolymer hardening and strength. The color of the geopolymers plays a significant role in hardening and strength. High strength geopolymer (92 MPa) was achieved through solar curing.